COMPLEXES OF SELECTED TRANSITION METAL IONS WITH N-MODIFIED GLYCINE AS LIGAND - SACALIS, Carmen; GOGA, Firuta; SOMESAN, Cristina (Studia Universitatis Babeș-Bolyai Chemia, 2018)
A novel series of transitional metal complexes of Cu(II), Co(II), Ni(II), Zn(II) and Fe(II) with N-modified glycine as ligand provide from phenylserinol were synthesized and characterized via elemental analysis, MS, IR, UV-VIS thermogravimetric analysis and ESR. The thermal stability of the ligand and synthesized complexes was discussed in the 20-1000 oC temperature range. The results indicate that the organic compound acts as a bidentate ligand, its coordination involving the carboxylate oxygen and the nitrogen atom belonging to the amino group of the glycine fragment. The shape of ESR spectrum for cooper complex at room temperature suggest an axial symmetry around the metallic ions (gII=2.427, g┴=2.063).